COX-2 Inhibition Reduces Brucella Bacterial Burden in Draining Lymph Nodes - Gagnaire, Aurélie; Gorvel, Laurent; Papadopoulos, Alexia; Von Bargen, Kristine; Mège, Jean-Louis; Gorvel, Jean-Pierre (Frontiers in Microbiology, 2016)
Brucella is a Gram-negative facultative intracellular bacterium responsible for a chronic disease known as brucellosis, the most widespread re-emerging zoonosis worldwide. Establishment of a T helper 1 (Th1)-mediated immune response characterized by the production of IL-12 and IFNγ is essential to control the disease. Leukotrienes derived from arachidonic acid (AA) metabolism are known to negatively regulate a protective Th1 immune response against bacterial infections. Here, using genomics approaches we demonstrate that Brucella abortus strongly stimulates the prostaglandin pathway in dendritic cells (DC). We also show an induction of AA production by infected cells. This correlates with the expression of Ptgs2, a gene encoding the downstream cyclooxygenase-2 (COX-2) enzyme in infected DC. By comparing different infection routes (oral, intradermal, intranasal and conjunctival), we identified the intradermal inoculation route as the more potent in inducing Ptgs2 expression but also in inducing a local inflammatory response in the draining cervical lymph nodes (CLN). NS-398, a specific inhibitor of COX-2 enzymatic activity decreased B. melitensis burden in the CLN after intradermal infection. This effect was accompanied by a decrease of Il10 and a concomitant increase of Ifng expression. Altogether these results suggest that Brucella has evolved to take advantage of the prostaglandin pathway in the harsh environment of the CLN in order to persist and subvert immune responses. This work also proposes that novel strategies to control brucellosis may include the use of COX-2 inhibitors.